Recharge and runoff under changing land use land cover in the Ramganga basin of Western Uttar Pradesh - Tripathi, S.S.; Isaac, R.K. (Indian Journal of Agroforestry, 2020)
In order to assess runoff and recharge pattern due to changing land use land cover (LULC) of the Ramganga river basin, a 31 years study from 1979 to 2009 was selected. The satellite images of the study area for three epochs (year 1979, 1990 and 2009) were acquired, analysed and classified under settlements, croplands, forest/plantations, water bodies, and waste-land classes. The result indicated increasing trend of crop land (from 60.6 to 83.6%) and built up area (from 4.1 to 6.4%), and decreasing trend of vegetation and plantation land (from 28.3 to 6%). The study showed the variation in runoff was significant which was depending upon rainfall occurrence, their temporal variation and temporal LULC dynamics. As evident from the fact that despite receiving lesser monsoon rainfall (865.2 mm) in 2009, significantly higher runoff (221.9 mm) was produced as compared to runoff (123.7 mm only) produced in 1990 with higher monsoon rainfall (950.5 mm). Similarly the percentage recharge had an increasing trend during 1979-1990 but was found to be declining during 1990-2009. Also quantum of recharge was higher till 1999 than quantum of runoff, but the trend reversed and runoff volume surpassed the recharge volume from 1999 and beyond. The results reveal that with increase in settlement, and crop land at the cost of forest land, the recharge rate has decreased and discharge rate (runoff) has increased, causing lowering of water table in the study area.